THE IMPLEMENTATION AND DEVELOPMENT OF PESANTREN CULTURE- BASED LEADERSHIP MODEL AT MA-NU BANAT KUDUS - Khoiri, Nur; Soegito, A.T.; Samsudi, Samsudi (The Journal of Educational Development, 2017)
Educational leadership is a key factor of success and would be effective and efficient when executed by leaders who are honest, responsible, transparent, intelligent, as well as understand their duties and obligations, understand their members, are able to motivate them, and possess various good properties. Islamic schools (henceforth: Madrasah) under the auspices of the Nahdlatul Ulama (MA-NU) Banat has particular characteristics that make it has special advantages which distinguish it from other madrasahs. MA-NU Banat is one of the best private madrasahs in Indonesia. The purpose of this study is to analyze leadership model of the principal of MA-NU Banat Kudus. The research method used was qualitative with the ethnographic approach. The findings show that the success of the principal leadership of MA-NU Banat is characterized by culture, values, and spirit of the Islamic boarding school (henceforth: pesantren). The pesantren culture itself is, in fact, the implementation of Islamic values. The characteristics of pesantren culture are not hesitant to adopt better new cultures, in addition to the maintenance a good old culture. The culture and old values that are applied in the principal leadership is istiqomah, dare to suffer to achieve the goal, qudwah hasanah, and mutual help and fraternal atmosphere, strict discipline, adherence to Kiai, high science culture, and working motivation worth of worship for achieving the pleasure of Allah. Developed culture is tauhid management and Total Quality Management (TQM)